Peritoneal tuberculosis mimicking ovarian carcinoma - Carvallo-Tapia, Cristina (2017)
Peritoneal tuberculosis is a common extrapulmonary site in females, mimicking an advanced ovarian malignancy. It is difficult to diagnose because it may produce massive ascites, and a gross peritoneal appearance similar to carcinomatosis. It requires confirmation by pathological studies and bacterial cultures, as there are not pathognomonic clinical, laboratory or radiologic findings. Early treatment usually is associated to good prognosis. A case of peritoneal tuberculosis with the classic triad (advanced-stage ovarian carcinoma-like ascites, abdominopelvic tumors and elevated serum CA-125 levels) is presented. Laparotomy showed abdominal and peritoneal nodules reported as granulomatous inflammation on biopsy. Patient started treatment and, on follow-up, symptoms and CA-125 levels normalized.